IMPACT OF HYPERTENSION AS AN ADDITIONAL RISK FACTOR IN CARDIORESPIRATORY STATUS OF POST SARS-COV-2 INFECTED SUBJECTS. (June 2022) - Kariori, Maria; Fragoulis, Christos; Polyzos, Dimitrios; Leontsinis, Ioannis; Grigoriou, Kalliopi; Drogkaris, Sotirios; Manta, Eleni; Tatakis, Fotis; Zammanis, Ioannis; Kouremeti, Maria; Siafi, Eirini; Konstantinidis, Dimitrios; et al.
Abstract : Objective: Few data have been published regarding the holistic approach of post-Covid patients, examining physical health. The purpose of our study was to examine the impact of arterial hypertension in the cardiopulmonary status of post-covid patients 3 months after the first day of infection. Design and method: All participants who recovered Covid-19 infection underwent cardiorespiratory exercise using either Bruce or modified Bruce protocol where all parameters were evaluated and transthoracic echocardiogram. The population was separated into two groups based on history of hypertension. Group I (n = 29) included hypertensive subjects and Group II (n = 75) included normotensive subjects. Results: A total of 104 patients were assessed 3 months after the onset of COVID-19 symptoms. We recorded a mean age of 49 ± 15 years, 50.5% of them were males, 8.7% had a history of coronary heart disease. Hypertensives had higher BMI (29.24 ± 24 vs 26.64 kg/m2, p < 0.01) and BSA (2.09 ± 0.25 vs. 1.95 ± 0.58, p = 0.001). They were hospitalized in higher percentage comparing to normotensives (72.4% vs. 41.3%, p < 0.01). Left atrial diameter (41 ± 6 vs. 35 ± 5.5 mm, p < 0.001) was significantly larger in hypertensives. Furthermore, A wave (79 ± 21 vs. 58 ± 18 cm/s, p < 0.001) and ratios of E/A (1.01 ± 0.42 vs. 1.28 ± 0.44, p < 0.01) and E/E' (7.3 ± 3.7 vs. 5.9 ± 4.3, p < 0.01) differed between two groups. Finally, LVEF (%) was significantly impaired in hypertensive comparing to normotesive subjects (53 ± 13% vs. 59 ± 7%). This finding was depicted in lower maximum oxygen consumption (VO2 22 ± 4.5 vs.28 ± 8 ml/kg/min, p < 0.001), metabolic equivalents (METS) at peak, 9.1 ± 3 vs. 14 ± 20, p < 0.001), maximum heart rate (maxHR 147 ± 17 vs. 165 ± 21 bpm, p < 0.001) and HR1st minute recovery (123 ± 28 vs. 138 ± 21 bpm, p: 0.02) comparing to normotensive. Systolic blood pressure (SBP, 180 ± 29 vs. 165 ± 25mmHg, p: 0.02) during the 1st minute of recovery was higher in hypertensives. Finally, the duration of exercise was significantly lower in patients with hypertension (7.3 ± 2.7 vs. 9 ± 4 min, p:0.02) Conclusions: the current study highlighted the negative impact of hypertension in the ability to exercise. Regardless of the disease severity, post-covid patients need a comprehensive approach for rehabilitation including the modification of risk factors like hypertension and obesity.